Dusk a novel - Jose, Francisco Sionil 1924- (Modern Library, 1992)
Opportunity knocks for a peasant boy in 19th century Philippines with the outbreak of the Spanish-American war. As an altar boy in his village, Istak is the only person able to read and write, and the Americans give him a job.